Analisis Faktor-Faktor Penyebab Rendahnya Minat Baca Siswa di Perpustakaan SD Negeri 1 Kelekar - Elin; Farhan yadi; Henni Riyanti; Elin, Elin; yadi, Farhan; Riyanti, Henni (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This study aims to determine what factors cause the low reading interest of students in the SD Negeri 01 Kelekar library. The research problem is what are the external and internal factors that cause students' low reading interest in the SD Negeri 01 Kelekar library. This research method will use descriptive qualitative research. The object of this research is students at SD Negeri 01 Kelekar. Data collection techniques used in this study were interviews, questionnaires and documentation. The data obtained is then analyzed by reducing, displaying and concluding. The results showed that there were several factors that influenced students' reading interest. External factors include family environmental factors that do not support and motivate students to read, curriculum and school education factors that are not conducive such as not providing a place to read other than the library, community infrastructure factors that do not support increasing interest in reading which gives examples of preferring to places of entertainment Instead of going to a bookstore, the factor of availability and accessibility of reading materials such as textbooks is incomplete, the collection of books students are looking for is also incomplete and the books in the library are not yet diverse. While internal factors include students' reading ability, namely there are students who have difficulty reading, there are still many students who do not understand the contents of the reading, students read books at the behest of the teacher, students read books not according to their needs, such as students prefer to read fables, stories and poetry rather than reading textbooks as well as students completing assignments looking at the internet instead of books